PENENTUAN HARGA JUAL KAMAR MELALUI IMPLEMENTASI ACTIVITY BASED COSTING SYSTEM PADA HOTEL NEW AYUDA 2 - Lestari, Destiana Puji; Afif, M. Nur; Triwidatin, Yuppy (Komunitas Manajemen Kompetitif, 2025)
Activity Based Costing is a method that can reduce cost distortions because it is caused by traditional cost accounting calculations. The calculation of the selling price of rooms at the New Ayuda 2 Hotel still uses traditional methods. The research is aimed at knowing how the difference in the calculation of selling prices between the Traditional method and the ABC Method. The data analysis method used in this study is a qualitative descriptive analysis with the calculation of the basic formula for determining the cost of goods using the Activity Based Costing method. The results of this study show that the calculations used at the New Ayuda 2 Hotel are still overcosting and undercosting when compared to the ABC system, because calculations using traditional methods only use one cost driver so that there are many cost distortions and result in irrelevant selling price calculations. Companies should reevaluate the cost-charging system in determining the selling price of rooms. Keywords: ABC Method, Traditional Method, Selling Price